«Conceptual framework» of ideology of the future in foreign social theory - Sarna, Aliaksandr J. (Journal of the Belarusian State University. Sociology, 2020)
The article attempts to identify and comparatively analyze the key ideological concepts of our time from the standpoint of their significance for the development of Western social theory, primarily the philosophy and sociology of technology. The material of futurology and forecasting shows the features of leading concepts, united by a common «conceptual framework» of ideas about the future development of society based on technological progress, which can be grouped into three areas which are retro-futurism, accelerationism and techno-mysticism. In such a perspective, retrofuturism is a look from the past to the future that has become relevant to the present, accelerationism is focused on a breakthrough from the present to the future, and techno-mysticism is trying to present the future as a new version of the past.